2019
DOI: 10.1002/acr.23795
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sports Habits, Leisure‐Time Physical Activity, and School‐Educational Physical Activity in Children With Juvenile Idiopathic Arthritis: Patterns and Barriers

Abstract: Objective. Juvenile idiopathic arthritis (JIA) may cause functional impairment and reduced time engaged in physical activity. The aim of this study was to investigate the habits of patients with JIA regarding participation in club sports, leisuretime physical activity, and school-educational physical activity and relate this to objectively measured physical activity using accelerometry and to compare the findings with those in healthy controls.Methods. Consecutive patients from the Aarhus University Hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…A majority of the children in our cohort participated fully in physical education, and only 2.9% reported no participation. In two recent reports from the Nordic countries both Risum et al and Nørgaard et al found similarly high participation rates in physical education for children and adolescents with JIA in, respectively, a Norwegian and a Danish controlled cross-sectional study [10, 11]. In a German registry study Milatz et al found that 66% of 5879 school-aged children with JIA participated fully in school sports, while 16% did not participate [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the children in our cohort participated fully in physical education, and only 2.9% reported no participation. In two recent reports from the Nordic countries both Risum et al and Nørgaard et al found similarly high participation rates in physical education for children and adolescents with JIA in, respectively, a Norwegian and a Danish controlled cross-sectional study [10, 11]. In a German registry study Milatz et al found that 66% of 5879 school-aged children with JIA participated fully in school sports, while 16% did not participate [34].…”
Section: Discussionmentioning
confidence: 99%
“…All forms of physical activity are now generally recommended and encouraged for children with JIA, replacing the previous traditions of giving advice to avoid certain activities [8]. Limited reports exist on participation in school and in physical education in JIA, and most reports are convenience-sampled, recruited from hospital cohorts, cross-sectional or with short follow-up time, and the studies are often small [3, 911].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity in JIA-populations has been studied previously [5, 7, 9, 5459]. However, the instruments used in these studies have not been specifically developed and tested among children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate physical activity (PA) is increasingly common in younger people [1, 2] and especially among children with chronic disability [35]. Juvenile Idiopathic Arthritis (JIA) is a systemic autoimmune disease with a prevalence of 0.16% in the Swedish population in children up to the age of 16 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zu ihnen gesellen sich im Rahmen chronischer rheumatischer Erkrankungen zudem besondere Herausforderungen, weshalb eine Risikoidentifikation und Prävention umso bedeutender sind. Neben Einblicken in Bewegungsprofile soll das im Wochenverlauf durchgeführte Aktivitätsmonitoring Risikogruppen für Bewegungsmangel identifizieren, Barrieren für körperlich aktives Verhalten aufdecken und Ansätze für Maßnahmen schaffen, die der Entwicklung von Begleiterkrankungen und negativen Folgen im späteren Leben entgegenwirken [19].…”
Section: Machine-learning-methodenunclassified